Application of Autologous Platelet-Rich Plasma on Tooth Extraction Site Prevents Occurence of Medication-Related Osteonecrosis of the Jaws in Rats - Toro, Luan Felipe [UNESP]; de Mello-Neto, João Martins [UNESP]; Santos, Fernanda Furuse Ventura dos [UNESP]; Ferreira, Letícia Chaves [UNESP]; Statkievicz, Cristian [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Issa, João Paulo Mardegan; Dornelles, Rita Cássia Menegati [UNESP]; Almeida, Juliano Milanezi de [UNESP]; Nagata, Maria José Hitomi [UNESP]; Garcia, Valdir Gouveia [UNESP]; Theodoro, Letícia Helena [UNESP]; et al. (Springer Nature, 2019)
This study evaluated the effects of local application of autologous platelet-rich plasma (PRP) on the tooth extraction site of rats presenting the main risk factors for medication-related osteonecrosis of the jaw (MRONJ). For seven weeks, senile rats were submitted to systemic treatment with vehicle (VEH and VEH-PRP) or 100 μg/Kg of zoledronate (ZOL and ZOL-PRP) every three days. After three weeks, the first lower molar was extracted. VEH-PRP and ZOL-PRP received PRP at the tooth extraction site. Euthanasia was performed at 28 days postoperatively. Clinical, histopathological, histometric and immunohistochemical analyses were carried out in histological sections from the tooth extraction site. ZOL showed lower percentage of newly formed bone tissue (NFBT), higher percentage of non-vital bone tissue (NVBT), as well as higher immunolabeling for TNFα and IL-1β. In addition, ZOL presented lower immunolabeling for PCNA, VEGF, BMP2/4, OCN and TRAP. VEH and ZOL-PRP showed improvement in the tooth extraction site wound healing and comparable percentage of NFBT, VEGF, BMP2/4 and OCN. Local application of autologous PRP proved a viable preventive therapy, which is safe and effective to restore tissue repair capacity of the tooth extraction site and prevent the occurrence of MRONJ following tooth extraction.